PENGARUH EFEKTIVITAS KOMITE AUDIT TERHADAP JANGKA WAKTU PELAPORAN KEUANGAN - Pratama, Jodi Setya; Rohman, Abdul (Diponegoro Journal of Accounting, 2015)
This research is a replica of Ika and Ghazali’s (2012). The difference from Ika and Ghazali’s is the subject, this research using financial company, and the sample has never done before. The effectiveness of the audit committee willl be expected to report company financial statements on time according to a predetermied time period. The goal of this research is to find out the relation between the effectiveness of the audit committee and company timelines, and to give descriptive evidence from effectiveness of the audit committe between timelines in finance companies that listed on Indonesia Stock Exchange. This research using financial reporting lead time as dependent variable and as the independent variables are the effectiveness of audit committte, financial conditions, the size of the companies, and the type of auditors. The sample in this research is 93 finance companies that listed on Indonesia Stock Exchange. The metodhs of this research are descriptive statistical analysis, classical assumption test (normality test, multicollinearity test, autocorrelation test, and heterocedastisity test), regression test, and hypothesis test. The result shows that 4 of independent variables in this research, only 3 independent variables that has impact to financial reporting lead time. However, only effectiveness of the audit committee that has biggest impact than the others.